Titania-Carbon Nitride Interfaces in Gold-Catalyzed CO Oxidation - Jiménez-Calvo, Pablo; Michel, Loïc; Keller, Valerie; Caps, Valérie (ACS Applied Materials and Interfaces, 2021)
Gold-catalyzed CO oxidation is a reaction of both practical and fundamental interest. In particular, rate-determining oxygen activation pathways have attracted a lot of attention. They have been found to depend on the surface chemistry of the catalyst support, titania providing the most active catalysts and carbon nitride leading to inactive catalysts. Here, we show that C3N4-TiO2 composites with rather similar surface chemistries can be engineered by using titania nanotubes as hard templates and by performing the polycondensation of melamine and dicyandiamide in air and in ammonia. By varying the C3N4 content from 2 to 75 wt %, the mesoporosity can be tuned from 8 to 40 nm. A systematic study of CO oxidation turnover numbers in the absence and in the presence of hydrogen over the composites loaded with well-calibrated 2-4 nm gold nanoparticles clearly shows that (1) the chemical composition of the support surface has much less impact on PROX (preferential oxidation of CO in excess hydrogen) than on dry CO oxidation, (2) NH2-terminated supports are as active as OH-terminated supports in PROX, (3) hydrogen/water-mediated CO oxidation pathways are active on C3N4-based Au catalysts, and (4) PROX activity requires a rather large porosity (40 nm), which suggests the involvement of much larger intermediates than the usually postulated peroxo-type species.
CRIS-Team Scopus Importer:2023-07-18
Keywords: carbon nitride; composites; gold catalysts; porosity; PROX; surface chemical composition; titania